Strategi Dinas Koperasi dan UMKM Kabupaten Karawang Dalam Pemberdayaan UMKM - Wulansari, Ajeng; Hakim, Lukmanul; Ramdani, Rachmat (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
This research is motivated by the fact that the MSME sector is the flagship in absorbing the workforce by moving local resources to support the regional economy. So that the empowerment carried out by the government must be maximized MSMEs can be competitive. This research aims to analyze strategies in the Office of Cooperatives and MSMEs in empowering and developing MSMEs. This research uses qualitative approach with case study method. Data collection techniques used are by interviews, observations and studies of documents / records / reports and legislation related to the problems studied. The focus of this research is based on the main dimensions of the strategy, namely innovation, market deference, reach and cost control. The results of this study show that the strategy of the Cooperative Office and MSME District in MSME empowerment has not run optimally. Because the guidance from this government can not be felt by all MSME actors. Furthermore, MSMEs do not get capital assistance from the local government, and in the meantime there are still many MSMEs that have not received guidance from the government. In addition, the government has helped to overcome the problem of budget constraints by inviting participation from state-owned enterprises and the private sector in the implementation of MSME empowerment.